Transformasi Spasial Hunian Pada Eks-Backpacker Enclaves Studi Kasus: Jalan Jaksa, Jakarta Pusat - Haristianti, Vika; Pratiwi, Wiwik Dwi (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2020)
This study aims to discover the extent of spatial transformation in residential areas on Jalan Jaksa, known as the ex-backpacker enclaves due to the concept of supply and demand. Spatial function, building facades, and corridors in residentials are the assessed variables. This study uses a qualitative method. Data collection is done by field observations, interviews, and literature review. The sampling method is using a non-random type or probability sample. The results of the analysis showed that from 26 samples there were 12 building/ residential samples (46.1%) that underwent installation, meaning that the building characteristics were adaptive, five buildings/ residential samples (19.2%) had insertion, meaning that the building was considered to be quite adaptive, and nine buildings/ residential samples (34 %) experiencing intervention, which means the building is not adaptive. In addition, the most changing category is the transformation in housing into multi-story buildings, lodging, and mixed-use buildings.